2007
DOI: 10.1103/physrevb.75.104119
|View full text |Cite
|
Sign up to set email alerts
|

Bond-order potential for simulations of extended defects in tungsten

Abstract: We present a bond-order potential (BOP) for the bcc transition metal tungsten. The bond-order potentials are a real-space semiempirical scheme for the description of interatomic interactions based on the tight-binding approximation. In the hierarchy of atomic-scale-modeling methods the BOPs thus provide a direct bridge between electronic-structure and atomistic techniques. Two variants of the BOP were constructed and extensively tested against accurate first-principles methods in order to assess the potentials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
112
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(130 citation statements)
references
References 120 publications
18
112
0
Order By: Relevance
“…The latter result agrees excellently not only with the atomistic simulations for the core structure of the screw dislocation in both Mo 20) and W, 21) but also with available DFT calculations 22) and explains the primary reasons for the breakdown of the Schmid law in bcc metals. More importantly we have shown that both the covalent character, originating from the angular dependence of unsaturated d-bonds, and the metallic character, coming from the screening effects of these bonds via quasi-free electrons, are equally important in an accurate description of the interatomic forces, which in turn control the dislocation behaviour in the non-magnetic bcc transition metals.…”
Section: )supporting
confidence: 82%
See 2 more Smart Citations
“…The latter result agrees excellently not only with the atomistic simulations for the core structure of the screw dislocation in both Mo 20) and W, 21) but also with available DFT calculations 22) and explains the primary reasons for the breakdown of the Schmid law in bcc metals. More importantly we have shown that both the covalent character, originating from the angular dependence of unsaturated d-bonds, and the metallic character, coming from the screening effects of these bonds via quasi-free electrons, are equally important in an accurate description of the interatomic forces, which in turn control the dislocation behaviour in the non-magnetic bcc transition metals.…”
Section: )supporting
confidence: 82%
“…This phenomena is the result of the screening of the bond integrals by the local environment, and our proposed analytic solution 19) for the screening function allows to solve the problem effectively. The screened bond-order potentials have been recently constructed for non-magnetic bcc-Mo 20) and bcc-W 21) and then tested and employed to study the core structure and glide of the screw dislocation with the Burgers vector b ¼ a 2 ½111. Figure 4 shows the [111] cross section of the {110} -surfaces for bcc-Mo calculated using screened BOP, unscreened BOP and compared with DFT calculations.…”
Section: Modelling Dislocation Behaviour In Magnetic Bcc-fementioning
confidence: 99%
See 1 more Smart Citation
“…This non-uniqueness of the R dependence of bond integrals, which manifests itself as discontinuities, results from the environmental dependence of bond integrals. Such discontinuities, found also in earlier studies, 30,31 originate from screening effects of electrons/orbitals (primarily of s-type) associated with atoms neighboring the dd bond considered. Instead of including explicitly the full sd basis this effect can be taken into account implicitly via screening of the dd bond integrals as proposed in Ref.…”
Section: Development Of the Bond-order Potentialsupporting
confidence: 73%
“…In order to smear the sharp cut-off of the energy at the Fermi level and to damp down the associated long-range Friedel oscillations a fictitious electronic temperature (T f ) is introduced; 34 as in the previous study 13, 31 we set k B T f = 0.1 eV where k B is the Boltzmann's constant. This method increases the rate of the convergence of both the energy and forces when employing BOPs.…”
Section: Development Of the Bond-order Potentialmentioning
confidence: 99%